2020
DOI: 10.1007/s12250-020-00242-1
|View full text |Cite
|
Sign up to set email alerts
|

SARS-Coronavirus-2 Nsp13 Possesses NTPase and RNA Helicase Activities That Can Be Inhibited by Bismuth Salts

Abstract: The ongoing outbreak of Coronavirus Disease 2019 has become a global public health emergency. SARScoronavirus-2 (SARS-CoV-2), the causative pathogen of COVID-19, is a positive-sense single-stranded RNA virus belonging to the family Coronaviridae. For RNA viruses, virus-encoded RNA helicases have long been recognized to play pivotal roles during viral life cycles by facilitating the correct folding and replication of viral RNAs. Here, our studies show that SARS-CoV-2-encoded nonstructural protein 13 (nsp13) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(167 citation statements)
references
References 28 publications
3
158
0
Order By: Relevance
“…It has been an early pharmaceutical target for SARS-CoV inhibition, with intention to reduce the unwinding ability of the viral helicase 28 . It was proven to be a promising molecular target for as the viral helicase could be inhibited without affecting the activity of the human helicase 29 , and this protein continues to be studied for the novel SARS-CoV-2 30,31 . However, the exact interactions between Nsp13 and MTOC have not been characterized to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…It has been an early pharmaceutical target for SARS-CoV inhibition, with intention to reduce the unwinding ability of the viral helicase 28 . It was proven to be a promising molecular target for as the viral helicase could be inhibited without affecting the activity of the human helicase 29 , and this protein continues to be studied for the novel SARS-CoV-2 30,31 . However, the exact interactions between Nsp13 and MTOC have not been characterized to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…A research report has shown that bismuth salts such as potassium citrate (BPC), ranitidine bismuth citrate (RBC), and bismuth citrate would inhibit NTPase and RNA helix-unwinding behaviors of SARS-CoV-2 nsp13. Among them, BPC or RBC can significantly impair SARS-CoV-2 nsp13-dependent NTPase and RNA helicase activities (Shu et al, 2020).…”
Section: Nonstructural Proteinsmentioning
confidence: 99%
“…DDX1 has been shown to enable the switch from discontinuous to continuous transcription in SARS-CoV-1 infection and its knockdown reduced the number of longer sub-genomic mRNA (sgmRNA) through interaction with the SARS-CoV-1 nucleocapsid protein N 60 and Nsp14 61 . It functions as a bidirectional helicase, which distinguishes it from the coronaviruses helicases, which can only unwind RNA in the 5' to 3' direction 62 , a very important function in highly structured RNA such SARS-CoV-2. DDX1 is also required for HIV-1 Rev as well as for avian coronavirus IBV replication and it binds to the RRE sequence of HIV-1 RNAs 1-3 , while CCNT1 binds to 7SK snRNA and regulates transactivation domain of the viral nuclear transcriptional activator, Tat 65,66 .…”
Section: Analysis Of Human Interactions With Sars-cov-2 Identifies Prmentioning
confidence: 99%